ANALISIS STANDARISASI PROSES PENGELASAN GMAW TERHADAP PENGELASAN BEJANA TEKAN JENIS SILO ASME - Hidayat, Ramdan; Rusyana, Mohammad Purwa (Universitas Nusa Putra, 2020)
Pressure vessel is a container for a fluid, both liquid fluid and pressurized gas. In designing a pressure vessel, there are several things that must be considered, namely the stress that appears on the vessel wall due to the pressure caused by the fluid in the vessel, the weight of the vessel itself, or due to pressure arising from external factors. The process of making pressure vessels is carried out using the rolling process and the assembly welding process. The welding process must be considered based on the level of density, leakage and at the same strength. Planning the welding procedure to be carried out on the pressure vessel, the first welding process carried out is Head, Shell 1 body, Shell 2 Body, Shell 3 cone, Shell 4 cone, and Bottom Plate. The material to be used is SA 516 GR 70 according to ASME (American Society of Mechanical Engineers) section II D. Welding process using GMAW (Gas Metal Arc Welding), welding connection planning, welding parameters and everything related to the welding process is determined and summarized on WPS (Welding Procedure Specification) based on ASME (American Society of Mechanical Engineers) section IX. Testing on the welding results is carried out in several stages starting from the penetrant test, radiography test, peneumatic test, and hydrostatic test. The test is carried out to determine the quality of the welding results. Then an analysis of the results of the welding that has been tested is carried out to really know the quality of the standardization used. Based on the results of several stages of testing on the GMAW (Gas Metal Arc Welding) welding process with the standardization used, there are still defects in the welding results.